Production process of high-performance hydrogen fuel cell noble metal catalyst

In the production process of precious metal catalysts for hydrogen fuel cells, noble metal precursors are formed using metal sources with specific atomic ratios and microwave heating, and the support is subjected to plasma and gradient heating treatment. Combined with high-temperature treatment, the problems of low catalytic efficiency and reduced stability of the catalyst are solved, and catalytic activity and battery durability are significantly improved.

CN119965288AActive Publication Date: 2025-05-09SHAANXI ZHUOYUE MATERIAL TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510450700.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2025-05-09
Estimated Expiration
2045-04-11

AI Technical Summary

Technical Problem

The catalytic efficiency of existing hydrogen fuel cells is low, and its stability decreases during long-term use, and the catalytic efficiency gradually decreases.

Method used

A high-performance hydrogen fuel cell precious metal catalyst production process is adopted, including dissolving platinum, lanthanum and zirconium sources in an organic solvent at a specific atomic ratio, and forming a precious metal precursor with microwave-assisted heating; plasma treatment and gradient heating treatment on the carrier to form a multi-stage pore structure; high-temperature treatment in an inert atmosphere to form a stable crystal structure.

Benefits of technology

The catalytic activity of the catalyst and the durability of the hydrogen fuel cell are significantly improved, the service life of the catalyst is extended, and the adsorption and activation ability of reactant molecules is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_9
    Figure SMS_9
Patent Text Reader

Abstract

The invention relates to the technical field of hydrogen fuel cells, and discloses a production process of a high-performance hydrogen fuel cell noble metal catalyst, which comprises the following steps: (1) preparing a noble metal precursor; (2) gradient modification of the carrier; (3) nano composite deposition; (4) performing high-temperature treatment; the production process of the high-performance noble metal catalyst for the hydrogen fuel cell has remarkable effects on improving the catalytic activity of the catalyst and the durability of the hydrogen fuel cell, and comprises the following steps: firstly, dissolving a platinum source, a lanthanum source and a zirconium source in an organic solvent according to a specific atomic ratio, and performing microwave-assisted heating to form a noble metal precursor; through microwave heating, all metal sources can be uniformly dispersed and rapidly react to form an alloy with a unique crystal structure and electronic properties. The addition of lanthanum and zirconium changes the electron cloud distribution of platinum, enhances the adsorption and activation capabilities on reactant molecules, and reduces the activation energy of the reaction, thereby improving the catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen fuel cells, in particular to a production process of a high-performance noble metal catalyst for hydrogen fuel cells. Background Art

[0002] As the global demand for clean energy grows, hydrogen fuel cells, as an efficient and environmentally friendly energy conversion device, have received extensive attention and research. Hydrogen fuel cells are power generation devices that directly convert the chemical energy of hydrogen and oxygen into electrical energy. Their working principle is based on the oxidation reaction of hydrogen under the action of the anode catalyst, releasing electrons and protons. The electrons form an electric current through the external circuit, and the protons reach the cathode through the proton exchange membrane, and react with oxygen under the action of the cathode catalyst to generate water. The whole process does not produce greenhouse gases and pollutants, and has the advantages of high energy conversion efficiency, low noise, and strong reliability. It has broad application prospects in transportation, distributed power generation, portable power sources and other fields.

[0003] Catalysts play a vital role in the working process of hydrogen fuel cells. Catalysts can reduce the activation energy of the reaction between hydrogen and oxygen, accelerate the electrode reaction, and thus improve the performance and efficiency of the battery. At present, precious metal catalysts, especially platinum-based catalysts, are widely used in hydrogen fuel cells due to their excellent catalytic activity and stability. Platinum-based catalysts can effectively promote the oxidation reaction of hydrogen and the reduction reaction of oxygen, enabling the battery to operate at a lower overpotential and improve the output voltage and power density of the battery.

[0004] However, existing hydrogen fuel cell precious metal catalysts have some obvious drawbacks, the most prominent of which is the low catalytic efficiency. Traditional catalyst preparation methods often result in a limited number of active sites in the catalyst, and the catalytic activity cannot be fully exerted. On the other hand, the catalyst is prone to decreased stability and gradually reduced catalytic efficiency during long-term use.

[0005] In order to solve the problem of low catalytic efficiency of existing hydrogen fuel cell catalysts, the present invention proposes a high-performance hydrogen fuel cell precious metal catalyst production process to solve the corresponding problem. Summary of the invention

[0006] In view of the problems in the prior art, the present invention provides a production process for high-performance hydrogen fuel cell precious metal catalysts.

[0007] The technical solution adopted by the present invention to solve the technical problem is: a production process of a high-performance hydrogen fuel cell precious metal catalyst, comprising the following steps: (1) Precious metal precursor: Platinum source, lanthanum source and zirconium source are dissolved in an organic solvent at an atomic ratio of 0.4-0.6:0.15-0.25:0.15-0.25, and heated to 460-500°C with the aid of microwaves for 20-25 minutes to obtain a precious metal precursor; (2) Carrier gradient modification: using The mixed gas is used as plasma to treat the activated carbon carrier with a power density of 70-130W / cm². After the plasma treatment, the activated carbon carrier is firstly subjected to liquid nitrogen quick freezing treatment at -196°C, kept warm for 30 minutes, then restored to 20°C, kept warm for 30 minutes, and then subjected to gradient temperature increase treatment from 20°C to 110°C, and finally returned to room temperature to obtain a modified carrier; (3) Nanocomposite deposition: The noble metal precursor and the modified support are mixed under the assistance of ultrasound at a frequency of 42 kHz, and then the solvent is removed by freeze drying to obtain a composite; (4) High temperature treatment: In an inert atmosphere, the temperature of the composite is raised to 950-1000°C at a rate of 4°C / min, kept at this temperature for 2-3 hours, then gradually cooled, kept at 160-170°C for 1.5 hours, and then returned to room temperature to obtain a precious metal catalyst.

[0008] As a further technical solution, the platinum source in step (1) is chloroplatinic acid, the lanthanum source is lanthanum nitrate, the zirconium source is zirconium nitrate, and the organic solvent is a mixed solution of polyethylene glycol and polyvinyl alcohol in a mass ratio of 1:2.

[0009] As a further technical solution, the microwave power of the microwave-assisted heating in step (1) is 400W.

[0010] As a further technical solution, the time for treating the activated carbon carrier with plasma in step (2) is 15-18 minutes.

[0011] As a further technical solution, the gradient heating rate in step (2) is 4-4.5°C / min.

[0012] As a further technical solution, the modified carrier in step (3) is mixed with the noble metal precursor at a mass ratio of 2.2-2.8:1.

[0013] As a further technical solution, the time for ultrasonic-assisted mixing in step (3) is 25-30 minutes, and the ultrasonic frequency is 40 kHz.

[0014] As a further technical solution, the inert atmosphere in step (4) is nitrogen or argon, and the gas purity is not less than 99.95%.

[0015] As a further technical solution, the gradient cooling rate in step (4) is 8°C / min.

[0016] Beneficial effects of the present invention: The high-performance hydrogen fuel cell precious metal catalyst production process of the present invention has a significant effect on improving the catalytic activity of the catalyst and the durability of the hydrogen fuel cell. First, the present invention forms a precious metal precursor by dissolving a platinum source, a lanthanum source, and a zirconium source in an organic solvent according to a specific atomic ratio and performing microwave-assisted heating. Microwave heating can make each metal source evenly dispersed and react quickly to form an alloy with a unique crystal structure and electronic properties. The addition of lanthanum and zirconium changes the electron cloud distribution of platinum, enhances the adsorption and activation ability of reactant molecules, reduces the activation energy of the reaction, and thus improves the catalytic activity; then the carrier is modified: with Plasma treatment of activated carbon carriers introduces abundant surface functional groups, increases the interaction between carriers and precious metals, and is conducive to the uniform loading of precious metals. Liquid nitrogen quick freezing and gradient temperature rise treatments form a multi-level pore structure on the carrier. The mesoporous structure provides a rapid diffusion channel for reactants and products, increases the contact opportunities between active sites and reactants, and further improves the catalytic efficiency. Subsequent ultrasonic-assisted mixing allows the precious metal precursors to be evenly dispersed on the modified carrier. During the freeze-drying process to remove the solvent, particle agglomeration is avoided, the size of platinum particles is effectively controlled, the number of active sites is increased, and the catalytic activity is improved. Finally, high-temperature treatment in an inert atmosphere further orders the alloy, forms a stable crystal structure, and enhances the activity and stability of the catalyst. Gradient cooling and staying in a specific temperature range help control crystal growth and defect formation, optimize the microstructure of the catalyst, and improve catalytic performance.

[0017] The catalyst structure is alloyed by a specific method, which improves the anti-poisoning and anti-oxidation capabilities of the catalyst and reduces the activity attenuation of the catalyst during use.

[0018] At the same time, the multi-level pore structure and surface functional groups of the carrier enhance the binding force between the carrier and the precious metal, preventing the migration and agglomeration of the precious metal particles during battery operation, thereby extending the service life of the catalyst.

[0019] In summary, the production process of the present invention significantly improves the catalytic activity of the catalyst and the durability of the hydrogen fuel cell through the synergistic effect of each step. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.

[0021] Embodiment 1

[0022] A high-performance hydrogen fuel cell precious metal catalyst production process comprises the following steps: (1) Preparation of precious metal precursors Chloroplatinic acid, lanthanum nitrate and zirconium nitrate were dissolved in a mixed solution of polyethylene glycol and polyvinyl alcohol in a mass ratio of 1:2 at an atomic ratio of 0.4:0.15:0.15. Microwave-assisted heating was performed under a microwave power of 400 W, and the mixed solution was heated to 460° C. and maintained for 20 minutes to obtain a noble metal precursor.

[0023] (2) Carrier gradient modification use The mixed gas was used as plasma, and the activated carbon carrier was plasma treated at a power density of 70W / cm² for 15 minutes; the activated carbon carrier treated with plasma was quickly frozen at -196°C in liquid nitrogen and kept warm for 30 minutes, then restored to 20°C and kept warm for 30 minutes; the temperature was increased from 20°C to 110°C at a rate of 4°C / min for gradient heating, and finally returned to room temperature to obtain a modified carrier.

[0024] (3) Nanocomposite deposition The modified support and the noble metal precursor were mixed at a mass ratio of 2.2:1, and ultrasonic-assisted mixing was performed for 25 minutes at an ultrasonic frequency of 40 kHz. After the mixing was completed, the solvent was removed by freeze drying technology to obtain a composite.

[0025] (4) High temperature treatment The composite was placed in an inert atmosphere of nitrogen with a purity of not less than 99.95%, and the temperature was raised to 950°C at a rate of 4°C / min and kept at that temperature for 2 hours. Then, the temperature was gradually lowered at a rate of 8°C / min, and the temperature was kept at 160°C for 1.5 hours, and finally returned to room temperature to obtain a high-performance hydrogen fuel cell precious metal catalyst.

[0026] Embodiment 2

[0027] A high-performance hydrogen fuel cell precious metal catalyst production process comprises the following steps: (1) Preparation of precious metal precursors Chloroplatinic acid, lanthanum nitrate and zirconium nitrate were dissolved in a mixed solution of polyethylene glycol and polyvinyl alcohol in a mass ratio of 1:2 at an atomic ratio of 0.5:0.2:0.2. Microwave-assisted heating was performed at a microwave power of 400 W, and the mixed solution was heated to 470° C. and maintained for 22 minutes to obtain a noble metal precursor.

[0028] (2) Carrier gradient modification use The mixed gas was used as plasma, and the activated carbon carrier was plasma treated at a power density of 90W / cm² for 16 minutes; the activated carbon carrier treated with plasma was quickly frozen at -196°C in liquid nitrogen and kept warm for 30 minutes, then restored to 20°C and kept warm for 30 minutes; the temperature was increased from 20°C to 110°C at a rate of 4.2°C / min for gradient heating, and finally returned to room temperature to obtain a modified carrier.

[0029] (3) Nanocomposite deposition The modified support and the noble metal precursor were mixed at a mass ratio of 2.4:1, and ultrasonic-assisted mixing was performed for 26 minutes at an ultrasonic frequency of 40 kHz. After the mixing was completed, the solvent was removed by freeze drying technology to obtain a composite.

[0030] (4) High temperature treatment The composite was placed in an inert atmosphere consisting of argon gas with a purity of not less than 99.95%, and the temperature was raised to 960°C at a rate of 4°C / min and kept at that temperature for 2.2 hours. Then, the temperature was gradually reduced at a rate of 8°C / min, and it stayed at 162°C for 1.5 hours before returning to room temperature to obtain a high-performance hydrogen fuel cell precious metal catalyst.

[0031] Embodiment 3

[0032] A high-performance hydrogen fuel cell precious metal catalyst production process comprises the following steps: (1) Preparation of precious metal precursors Chloroplatinic acid, lanthanum nitrate and zirconium nitrate were dissolved in a mixed solution of polyethylene glycol and polyvinyl alcohol in a mass ratio of 1:2 at an atomic ratio of 0.55:0.22:0.22. Microwave-assisted heating was performed under a microwave power of 400 W, and the mixed solution was heated to 490° C. and maintained for 24 minutes to obtain a noble metal precursor.

[0033] (2) Carrier gradient modification use The mixed gas was used as plasma, and the activated carbon carrier was plasma treated at a power density of 110W / cm² for 17 minutes; the activated carbon carrier treated with plasma was quickly frozen in liquid nitrogen at -196°C and kept warm for 30 minutes, then restored to 20°C and kept warm for 30 minutes; the temperature was increased from 20°C to 110°C at a rate of 4.4°C / min for gradient heating, and finally returned to room temperature to obtain a modified carrier.

[0034] (3) Nanocomposite deposition The modified support and the noble metal precursor were mixed at a mass ratio of 2.6:1, and ultrasonic-assisted mixing was performed for 28 minutes at an ultrasonic frequency of 40 kHz. After the mixing was completed, the solvent was removed by freeze drying technology to obtain a composite.

[0035] (4) High temperature treatment The composite was placed in an inert atmosphere of nitrogen with a purity of not less than 99.95%, and the temperature was raised to 980°C at a rate of 4°C / min and kept at that temperature for 2.8 hours. Then, the temperature was gradually lowered at a rate of 8°C / min, and stayed at 168°C for 1.5 hours before returning to room temperature to obtain a high-performance hydrogen fuel cell precious metal catalyst.

[0036] Embodiment 4

[0037] A high-performance hydrogen fuel cell precious metal catalyst production process comprises the following steps: (1) Preparation of precious metal precursors Chloroplatinic acid, lanthanum nitrate and zirconium nitrate were dissolved in a mixed solution of polyethylene glycol and polyvinyl alcohol in a mass ratio of 1:2 at an atomic ratio of 0.6:0.25:0.25. Microwave-assisted heating was performed under a microwave power of 400 W, and the mixed solution was heated to 500° C. and maintained for 25 minutes to obtain a noble metal precursor.

[0038] (2) Carrier gradient modification use The mixed gas was used as plasma, and the activated carbon carrier was plasma treated at a power density of 130W / cm² for 18 minutes; the activated carbon carrier treated with plasma was quickly frozen at -196°C in liquid nitrogen and kept warm for 30 minutes, then restored to 20°C and kept warm for 30 minutes; the temperature was increased from 20°C to 110°C at a rate of 4.5°C / min for gradient heating, and finally returned to room temperature to obtain a modified carrier.

[0039] (3) Nanocomposite deposition The modified support and the noble metal precursor were mixed at a mass ratio of 2.8:1, and ultrasonic-assisted mixing was performed for 30 minutes at an ultrasonic frequency of 40 kHz. After the mixing was completed, the solvent was removed by freeze drying technology to obtain a composite.

[0040] (4) High temperature treatment The composite was placed in an inert atmosphere consisting of argon gas with a purity of not less than 99.95%, and the temperature was raised to 1000°C at a rate of 4°C / min and kept at that temperature for 3 hours. Then, the temperature was gradually lowered at a rate of 8°C / min, and stayed at 170°C for 1.5 hours before returning to room temperature to obtain a high-performance hydrogen fuel cell precious metal catalyst.

[0041] Comparative Example 1: The difference from Example 1 is that no treatment is performed on the activated carbon carrier.

[0042] Comparative Example 2: The difference from Example 1 is that the activated carbon carrier is not subjected to plasma treatment.

[0043] test Oxygen reduction reaction (ORR) activity test Test method: Electrode preparation: The catalysts of the examples and comparative examples were prepared into rotating ring disk electrodes (RRDE) of the same specifications.

[0044] Test conditions: Using O2-saturated 0.1M KOH electrolyte, cyclic voltammetry scans were performed at 1600rpm in the voltage range of 0.6-1.0V to measure the half-wave potential. : : Reflects the ORR kinetic activity of the catalyst. The lower the voltage, the higher the activity. Table 1

[0045] It can be seen from Table 1 that the hydrogen fuel cell noble metal catalyst prepared by the present invention has high catalytic performance.

[0046] Fuel cell durability testing Single cell assembly: The catalysts of the examples and comparative examples are assembled with a proton exchange membrane and a gas diffusion layer into a membrane electrode assembly (MEA).

[0047] Test conditions: In H2 / O2 (1:1) atmosphere, operate at a constant voltage of 0.6V, gradually increase the current density to 0.8A / cm², and evaluate performance degradation after 30,000 cycles.

[0048] Activity retention rate: the ratio of the current density at 0.6V after cycling to the initial value: Table 2 Activity retention rate% Example 1 88.2 Example 2 88.3 Example 3 88.6 Example 4 88.9 Comparative Example 1 63.5 Comparative Example 2 75.7 It can be seen from Table 2 that the hydrogen fuel cell precious metal catalyst prepared by the present invention can improve the durability of the hydrogen fuel cell.

[0049] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-performance hydrogen fuel cell precious metal catalyst production process, characterized in that: The following steps are involved: (1) Precious metal precursor: Platinum source, lanthanum source and zirconium source are dissolved in an organic solvent at an atomic ratio of 0.4-0.6:0.15-0.25:0.15-0.25, and heated to 460-500°C with the aid of microwaves for 20-25 minutes to obtain a precious metal precursor; (2) Carrier gradient modification: using The mixed gas is used as plasma to treat the activated carbon carrier with a power density of 70-130W / cm². After the plasma treatment, the activated carbon carrier is firstly subjected to liquid nitrogen quick freezing treatment at -196°C, kept warm for 30 minutes, then restored to 20°C, kept warm for 30 minutes, and then subjected to gradient temperature increase treatment from 20°C to 110°C, and finally returned to room temperature to obtain a modified carrier; (3) Nanocomposite deposition: The noble metal precursor and the modified support are mixed under the assistance of ultrasound at a frequency of 42 kHz, and then the solvent is removed by freeze drying to obtain a composite; (4) High temperature treatment: In an inert atmosphere, the temperature of the composite is raised to 950-1000°C at a rate of 4°C / min, kept at this temperature for 2-3 hours, then gradually cooled, kept at 160-170°C for 1.5 hours, and then returned to room temperature to obtain a precious metal catalyst.

2. The production process according to claim 1, characterized in that: The platinum source in step (1) is chloroplatinic acid, the lanthanum source is lanthanum nitrate, the zirconium source is zirconium nitrate, and the organic solvent is a mixed solution of polyethylene glycol and polyvinyl alcohol in a mass ratio of 1:

2.

3. The production process according to claim 1, characterized in that: The microwave power of the microwave-assisted heating in step (1) is 400W.

4. The production process according to claim 1, characterized in that: The time for treating the activated carbon carrier with plasma in step (2) is 15-18 minutes.

5. The production process according to claim 1, characterized in that: The rate of the gradient heating in step (2) is 4-4.5°C / min.

6. The production process according to claim 1, characterized in that: The modified carrier in step (3) is mixed with the noble metal precursor at a mass ratio of 2.2-2.8:

1.

7. The production process according to claim 1, characterized in that: The time of ultrasonic-assisted mixing in step (3) is 25-30 minutes, and the ultrasonic frequency is 40 kHz.

8. The production process according to claim 1, characterized in that: In step (4), the inert atmosphere is nitrogen or argon, and the gas purity is not less than 99.95%.

9. The production process according to claim 1, characterized in that: The gradient cooling rate in step (4) is 8°C / min.

Citation Information

Patent Citations

  • Plate-shaped catalyst product and method for manufacturing same

    CN103747874A

  • Macroscopic body divided into multiple regularly-arranged tunnels by multiple films and manufacturing method thereof

    CN103979522A

  • Preparation method of plasma-based supported noble metal catalyst

    CN112246288A

  • Selective hydrogenation catalyst as well as preparation method and application thereof

    CN112916022A

  • Preparation method of fuel cell alloy catalyst for enhancing anchoring effect of carrier

    CN115579482A